Exploratory Multicriteria Decision Analysis of Utility‐Scale Battery Storage Technologies for Multiple Grid Services Based on Life‐Cycle Approaches. Issue 11 (23rd December 2019) - Baumann, Manuel; Peters, Jens; Weil, Marcel
Abstract : Herein, a multicriteria decision‐making analysis (MCDA) of eight different utility‐scale battery storage technologies for four different application areas, involving 72 relevant stakeholders from industry and academia for criteria selection and weighting, is presented. The assessment is conducted for economic, environmental, technological, and social criteria using a combination of the analytic hierarchy process and technique for order preference by similarity to ideal solution. It includes a full life‐cycle costing and life‐cycle assessment using current data. Indicative rankings show that most lithium‐ion batteries can be recommended for all application areas. Lead‐acid batteries achieve rather low scores depending on the viewed application, but including a recycling scenario for this technology might lead to significant changes in final scores and rankings. This is also true for the redox flow battery. Furthermore, the weights provided by the stakeholders are very dispersing, leading to a low consensus about the relevance of the used criteria. In particular, social criteria are not well differentiated in the current state and do not add significant distinguishing features between different battery technologies. Abstract : Multicriteria decision‐making analysis (MCDA) including life‐cycle approaches and stakeholder input can provide case‐specific decision support for the selection of batteries for grid services. Considered battery technologies score differently depending on the application. Lithium‐ion batteries turn out as all‐rounders, but a detailed view on recycling is required for all technologies. Furthermore, several tripping points have to be addressed in an MCDA assessment.